Modelling the relationship between relative load and match outcome in junior tennis players - Myers, N. L.; Morrow, R.; Farnsworth II, J. L (Journal of Human Sport & Exercise, 2022)
The acute:chronic workload ratio (ACWR) is a metric that can be used to monitor training loads during sport. Over the last decade researchers have investigated how this metric relates to injury, yet little consideration has been given to how this metric interacts with performance. Two prospective longitudinal studies were implemented investigating internal and external ACWRs and match outcome in junior tennis players. Forty-two and 24 players were recruited to participate in the internal and external load studies, respectively. Internal load was measured using session rate of perceive exertion, while external load was defined as total swing counts. The main dependent variable was tennis match performance which was extracted from the universal tennis rating website. The ACWR for internal and external load were the primary independent variables. Acute load was defined as the total load for one week, while a 4-week rolling average represented chronic load. There were no significant associations between internal (p-value = .23) or external (p-value = .81) ACWR and tennis match performance as assessed by multivariate regressions. The ACWRs in these datasets were close to 1.00, thus a balanced training load was undertaken by these athletes upon entering match play but was not related to match success.